Medial Meniscal Allograft Transplantation - Jordan D. Walters MD; Brian C. Werner MD (SAGE Publishing, 2021)
Background: This technique video reviews medial meniscal allograft transplantation (MAT) using a representative case example. Indications: Medial meniscal allograft transplantation is indicated in symptomatic patients with a deficient medial tibiofemoral compartment that has not progressed to arthritic changes. Concomitant procedures to address focal cartilage defects, ligamentous laxity, and/or limb malalignment should be performed prior to MAT or in the same surgical setting. Technique Description: Preoperative workup includes magnetic resonance imaging (MRI), prior arthroscopic pictures, and sizing radiographs. The Pollard radiographic method measures for the appropriate cryopreserved allograft size. Arthroscopic instruments remove residual meniscal tissue to a 1 mm base around the capsule. Percutaneous lengthening of the medial collateral ligament (MCL) at its femoral attachment aids visualization/instrumentation. This technique employs 8-mm bone plugs for anterior and posterior meniscal root fixation. Tunnels size 8.5 mm diameter and 10 mm depth are created. Once the meniscal allograft is placed in the joint, inside-out sutures are placed throughout the meniscal body. Sutures from the meniscal roots are secured with an anchor in the anterior proximal tibia. Results: There are numerous outcomes studies of meniscal allograft transplantation with a reported overall graft survivorship of roughly 70% at 10 years and 60% at 15 years follow-up. Discussion/Conclusion: Meniscal allograft transplantation is a temporizing measure that provides good midterm clinical results, although long-term failure rates increase incrementally. Most studies suggest return to sport is possible although activity modification is recommended.